PRODUKSI DEKSTRIN UBIKAYU MELALUI METODE GELATINISASI SEBAGIAN MENGGUNAKAN ROTARY DRUM - Surfiana Surfiana; Siti Nurdjanah; Nurbani Kalsum; Liana Verdini (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
This research was aimed to obtain the optimum condition and characteristics of dextrin processed from tapioca(cassava starch) by using partial gelatinization using drum dryer. This experiment was arranged in randomized compelete block design with three factors and three replications. The first factor was (V) cassava varieties, which consisted of Cassesart/UJ-5 (V1) and Thailand/UJ-3 (V2). The second factor (K) was the concentration which consisted of three levels : 30 % (K1), 35 % (K2), and 40 % (K3). The third factor (T) was the temperature of the partial gelatinization which consisted of three temperature levels that were 80o C (T1), 90oC(T2), and 100oC(T3). Characterization was conducted on dextrin processed from tapioca included chemical and physical characteristics (water absorption, and water solubility). The results showed that the varieties of cassava, concentration, and temperature have significant effect on dextrin saccharide composition, solubility in water, and swelling power. Thailand variety, 35 % concentration, and processing temperature of 90o C produced dextrin with better functional characteristics , which were 24 % of dextrin composition, 77,15 % of solubility, and 6,89 % of swelling power. Key words : Cassava, dextrin, parsial gelatinazation, rotary drum.